Analysis Of Factors Influencing The Sustainability Report Disclosure (Case Study Of Mining-Sector-Companies-Listed-In-Indonesia-Stock Exchange From 2015 To 2019) - et. al., Anissa Rizkia Saepudin, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to analyze factors of the sustainability report disclosure. The independent variables were Board Commissioners Size, Proportion of Independent Commissioner, Managerial Capital Ownership, Firm Size, and Profitability. The dependent variable is the Sustainability Report. The population in this study was the mining sector listed in Indonesia Stock Exchange in the period 2015 - 2019. Based on the purposive sampling method, 6 companies published sustainability reports consistently. This study analyzes the company's annual reports and sustainability reports. The analysis techniques for this research were panel data regression methods. The results of this study revealed that the Board Commissioner Size, Proportion of Independent Commissioner, Managerial Capital Ownership, and Profitability did not significantly affect the sustainability report disclosure. While the variable of firm size had a significant effect on the disclosure of sustainability reports